The Influence of Promotion, Price Discount, and Shopping Lifestyle on Impulse Buying in E-Commerce on Shopee (a Case Study Among Students at Muhammadiyah University Pontianak) - Rahmawati, Nanda; Archie, Ananda (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the influence of promotion, price discount, and shopping lifestyles on impulse buying among Shopee e-commerce users, with a focus on students at Muhammadiyah University Pontianak. The method used in this study is a causal associative approach. The sample consisted of 100 respondents using purposive sampling. To test the research instruments, validity tests, reliability tests, and classical assumption tests were conducted, including normality tests, linearity tests, and multicollinearity tests. Hypothesis testing was performed using multiple linear regression analysis, correlation coefficients, determination coefficients, simultaneous tests, and partial tests. The results of the multiple linear regression showed the regression equation Y=1.314+0.142X1+0.361X2+0.190X3. The correlation coefficient analysis yielded a value of 0.604, indicating a strong relationship between promotion, price discount, and shopping lifestyle on impulse buying. The coefficient of determination shows a value of 0.365, meaning that 36.5% of the impulse buying variable can be explained by the three variables, while 63.5% is influenced by other factors not examined in this study. The simultaneous test results indicate that, simultaneously, promotions, price discounts, and shopping lifestyle significantly influence impulse buying among students at Muhammadiyah Pontianak University. The partial test results show that the variables of promotion, price discount, and shopping lifestyle have a positive and significant influence on impulse buying.